Advancing Sustainable Agriculture: Integrating Biotechnology, Genetic Engineering, and Environmental Sciences for Improved Crop Yield and Ecosystem Health - Dr Sunil Kumar,; Dr. R. Bharath Kumar,; Sambhani Naga Gayatri,; Ashutosh C Kakde,; Dr. Atowar ul Islam,; Dr. Rajeeb Lochan Moharana, (The Bioscan, 2025)
Biotechnology, genetic engineering, and environmental sciences working together create new ways to make farming more sustainable. This study looks at new ways to boost crop production while making good use of resources and keeping the environment healthy. Our analysis combined Genetic Algorithm, Neural Networks, Support Vector Machines, and Random Forest to anticipate crop behaviors and maximize yield through environmental simulations. Our lab tests revealed a 22% crop production enhancement alongside 30% water usage reduction and 25% better soil quality - outperforming traditional approaches by 15-18% in parallel situations. Recent advances in nanotechnology and bioengineering enhanced plant survival under environmental stress and improved their nitrogen uptake performance by 18%. Through microbe-based innovation plants can deal with dry conditions and utilize nutrients more effectively by 20%. The research demonstrates that using data science together with various professional specialties leads to better solutions for confronting farming issues like climate change and resource management. The study combines environmental science with advanced data tools to deliver useful information for better farming methods. The research demonstrates how better methods in crop farming and environmental care will establish reliable agricultural systems for global food production.